Assessment of Growing Stock, Above Ground Biomass and Sequestered Carbon in Sal Dominated Kushmi Forest Gorakhpur - Chaurasia, Sandeep; Kumar, Hemant; Dubey, Kumud; Agarwal, Yogesh Kumar (Indian Forester, 2020)
The intergovernmental panel on climate change identified that forest growing stocks is the largest terrestrial carbon sink in terrestrial ecosystem and account for nearly 90% of all leaving terrestrial biomass. The amount of carbon stocked by a forest can be estimated from the biomass accumulation since approximately half of forest dry biomass weight constitutes carbon. Present study was carried out during 2017-18 in Kushmi Sal Forest near Gorakhpur, Uttar Pradesh. The whole forest is a best example of plantation forest mainly dominated by Shorea robusta. The other associate species like Tectona grandis, Syzygium cumini, Terminalia arjuna, Albizia lebbeck, Dalbergia sissoo, Eucalyptus sp., Madhuca indica, Azadirachta indica, and Bombax ceiba were also found in certain part in patches or in scattered form. Present research is an attempt in this direction to quantify the growing stock and carbon stock of Kushmi forest. The woody volume of tress for each species was calculated using volume equation developed by FSI for various species. The total area of Kushmi forest is 3207.10 ha (Tilkonia forest range) comprises total number of forest tree 580480. The maximum number of tree belongs to species Shorea robusta (402560) followed by Tectona grandis (80640) whereas the least numbers of trees of species Bombax ceiba (5052). The maximum diameter was recorded in Madhuca indica (1.53m) followed by Azadirachta indica (1.38m) while minimum diameter was recorded in Dalbergia sissoo (0.51m). The total growing stock was found in Shorea robusta (7158573.87m3 ) followed by Tectona grandis (690116.45m3) while minimum 3 was found in Dalbergia sissoo (19966.64m3). The total above ground carbon stock in the research area was recorded 3.727 Mt C.